Analisis Penerapan Model UTAUT terhadap Kinerja Sistem E-Office di Pemerintah Kabupaten Mojokerto - Azzkri, Achmad Fadillah; Anugrah, Chandra Sukma; Fibrian, Ivan Dwi (Universitas Multi Data Palembang, 2025)
The development of information technology encourages the modernization of government administration, including the implementation of E-Office in Mojokerto District Government. This study was conducted because of the importance of evaluating technology acceptance to ensure E-Office has a positive impact as expected. This study aims to analyze user acceptance of E-Office with the Unified Theory of Acceptance and Use of Technology (UTAUT) approach and identify variables that affect user acceptance. Partial Least Squares-Structural Equation Modeling (PLS-SEM) method is used to analyze the relationship between variables in the UTAUT model, namely performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention, and use behavior. The results showed that Behavioral Intention is the variable that most significantly affects the behavior of using the E-Office application, while Effect Expectancy, Social Influence, and Facilitating Conditions have no significant effect. Users have a high intention to use the system because they believe that the system can improve performance. This research provides strategic recommendations for improving technology acceptance in the government sector by focusing on strengthening user intentions, which is a key factor in the successful implementation of the E-Office system.